Efficient, Glucose Responsive, and Islet-Specific Transgene Expression by a Modified Rat Insulin Promoter - Chai, Renjie (2009)
This study was done to improve efficiency and islet specificity of the rat insulin promoter (RIP). Various rat insulin promoter lengths were prepared and tested in vitro to drive luciferase reporter gene expression in INS1-cells, alpha-cells, acinar cells, ductal cells, and fibroblasts. The CMV promoter was used as a positive control. In addition, the DsRed reporter gene was administered in vivo to rat pancreas by ultrasound-targeted microbubble destruction (UTMD). Confocal microscopy was used to detect the presence and distribution of DsRed within the pancreas after UTMD. A modified RIP3.1 promoter, which includes portions of the insulin gene after its transcription start site is 5-fold more active in INS-1 cells than the full length RIP promoter or the CMV promoter. RIP3.1 is regulated by glucose level and various islet transcription factors in vitro, and exhibits activity in alpha-cells, but not exocrine cells. In vivo delivery of RIP3.1-DsRed resulted in expression of DsRed protein in beta-cells, and to a lesser extent alpha cells under normal glucose conditions. No DsRed signal was present in exocrine pancreas under RIP3.1. A modified rat insulin promoter, RIP3.1, efficiently and specifically directs gene expression to endocrine pancreas.